Obtaining Primary Behavioral Data for Transportation Demand Estimates and Social Variables by means of Experimental Scenarios as an Empirical Tool for the Application of Transportation Planning and Public Policies in the Basin - Matute, Cristian Eduardo Zamora; Aray, Dario Alberto Ordoñez; Edwin Paúl Feijoo Criollo (Migration Letters, 2023)
The article highlights the growing issue of congestion and traffic caused by the increasing number of cars in cities. It emphasizes the need for public institutions to develop strategies for sustainable mobility and address daily traffic problems. Despite efforts to discourage motor vehicle use, data from the Municipal Traffic Department of Cuenca shows a significant rise in the number of vehicles, with 2021 marking a historical peak. The study identifies preferences and choices of transportation modes, as well as the reasons for their use, with private vehicles satisfying the mobility needs of only 30% of the population. The findings indicate that traffic issues are particularly associated with private vehicles. The article concludes by presenting a demand estimate involving various modes of transport and their associated attributes. It emphasizes the value of travel time savings, waiting time, and blocks walked as significant factors in transportation projects. The research also explores the impact of weather variations on people’s valuations of these factors. Furthermore, the study calculates the elasticities of transport modes in response to various policy scenarios, highlighting the sensitivity of these modes to fare changes, waiting times, travel costs, and parking costs. The research confirms that price increases generally lead to decreased demand, while service improvements or reduced travel times increase the likelihood of using a particular mode of transport. The article provides valuable insights for transportation planning and policy development.